2022
DOI: 10.1039/d2gc00606e
|View full text |Cite
|
Sign up to set email alerts
|

Separation of nickel from cobalt and manganese in lithium ion batteries using deep eutectic solvents

Abstract: A cornerstone of the decarbonisation agenda is the use of lithium ion batteries, particularly for electric vehicles. It is essential that effective recycling protocols are developed and this includes the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 55 publications
1
31
0
Order By: Relevance
“…The existence of [CoCl 4 ] 2– proved the formation of Cl 3 – , which was proposed to play a pivotal role in the oxidative dissolution of LIB metal oxides . In previous studies using the conventional heating method, ChCl–OA could leach 85% of Co under the optimum conditions. ,, However, leaching Co using the microwave heating method made a difference. Therefore, it was necessary to determine whether the reason for the low Co extraction efficiency at different temperatures was the insufficient reducing capacity of the DES or the insoluble oxalate precipitates generated by reduced Co 2+ …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of [CoCl 4 ] 2– proved the formation of Cl 3 – , which was proposed to play a pivotal role in the oxidative dissolution of LIB metal oxides . In previous studies using the conventional heating method, ChCl–OA could leach 85% of Co under the optimum conditions. ,, However, leaching Co using the microwave heating method made a difference. Therefore, it was necessary to determine whether the reason for the low Co extraction efficiency at different temperatures was the insufficient reducing capacity of the DES or the insoluble oxalate precipitates generated by reduced Co 2+ …”
Section: Resultsmentioning
confidence: 99%
“…If needed, ChCl would be transformed into a vacuum oven overnight before preparing the DESs. A transparent and uniform DES system could be obtained by mixing ChCl and OA with a 1:1 molar ratio at 80 °C in a magnetic stirring water bath until a colorless homogeneous liquid formed. , Deionized water with different molar ratios was added as well. The molar ratio of added water to ChCl ranged from 0 to 8.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al also revealed that 89.1 wt % of Co was extracted when the LiCoO 2 cathode material was leached in ChCl–urea at 170 °C for 12 h with vigorous stirring . DES is proven to be a feasible approach for extracting critical metals from spent LIBs. However, its application is still limited by high operation temperature (180–220 °C) and long reaction time (18–24 h), associated with high energy consumption and production cost . In addition, the diversity of constituent elements and differences in the crystal structures of metal compounds would limit the selectivity in extracting critical metals from multisource and heterogeneous hybrid cathode materials, thus lowering the feasibility of solvometallurgy systems.…”
Section: Introductionmentioning
confidence: 99%
“…DESs are the liquid mixture of two or more compounds interacting through hydrogen bonds or halogen bonds. ,, The individual compounds are known as hydrogen bond donors (HBDs) or hydrogen bond acceptors (HBAs). Not only DESs show similar benign properties to the ionic liquids (ILs), such as low volatility, low flammability, and low melting point, but also it has the unique advantages of a simple synthesis procedure, high atomic utilization rate, and high product purity. Due to these favorable properties of DESs, they have been paid much attention in many areas. , …”
Section: Introductionmentioning
confidence: 99%